Young mums are rebuilding the spurdog stock (Squalus acanthias L.) in Norwegian waters. (5th August 2019) - Albert, Ole Thomas; Junge, Claudia; Myrlund, Marlén Knutsen
Abstract: Based on a sampling programme of spurdog ( Squalus acanthias ) from Norwegian fishery landing sites during 2014–2018, the spatio-temporal distribution, size, sex, and age composition of this previously heavily overfished shark is described and compared to the situation before the stock collapsed. Among those spurdog large enough to be caught in the fisheries, all size groups, both sexes, and all maturity stages were present in the 3948 individuals examined from the landing sites. This shows that spurdog utilizes Norwegian coastal waters year-round and for their whole life cycle. The age composition was similar for males and females, and both were observed from age 3 up to the mid-30s. Age at 50% maturity was 9.5 years for females, and near-term females were mostly found during August–January without any clear latitudinal difference. The stock is largely dominated by younger age groups, and the mean age of late gravid females was 15 years, with an interquartile range of 12–16 years. This compares to a generation time of 25 years used elsewhere and is considered to be indicative of sound recruitment of a rebuilding stock. Analyses across age groups indicate that the recent rate of increase in year-class size for adult age groups is much larger than estimated in the assessments. Possible reasons for this and the need for further studies are discussed.